Discrete Sliding Mode Control for Hypersonic Cruise Missile - Yong Hua Fan; Peng Peng Yan; Fan Wang; Hong Yang Xu (Discrete Dynamics in Nature and Society)
A discrete variable structure control (DVSC) with sliding vector is presented to track the velocity and acceleration command for a hypersonic cruise missile. In the design an integrator is augmented to ensure the tracking with zero steady-state errors. Furthermore the sliding surface of acceleration is designed using the error of acceleration and acceleration rate to avoid the singularity of control matrix. A proper power rate reaching law is utilized in this proposal; therefore the state trajectory from any initial point can be driven into the sliding surface. Besides, in order to validate the robustness of controller, the unmolded dynamic and parameter disturbance of the missile are considered. Through simulation the proposed controller demonstrates good performance in tracking velocity and acceleration command.